Computing pth roots in extended finite fields of prime characteristic p ≥ 2. Issue 9 (8th April 2016) - Repka, M.
Abstract : Direct computation of p th roots in extended finite fields of characteristic p ≥ 2 is introduced, wherein the reduction polynomial is irreducible and can be even random. Proposed method works in any case of p ≥ 2 and finite field extension. This method is the most efficient, it is even more efficient than the method, which is widely used, based on inversion of squaring matrix utilised in the case of p = 2. This method is more efficient regarding the computation and storing of the matrix as well as the computation of the roots.